The PP1 binding code: a molecular‐lego strategy that governs specificity. (21st March 2012) - Heroes, Ewald; Lesage, Bart; Görnemann, Janina; Beullens, Monique; Van Meervelt, Luc; Bollen, Mathieu
<x xml:space="preserve">Abstract</x> Ser/Thr protein phosphatase 1 (PP1) is a single‐domain hub protein with nearly 200 validated interactors in vertebrates. PP1‐interacting proteins (PIPs) are ubiquitously expressed but show an exceptional diversity in brain, testis and white blood cells. The binding of PIPs is mainly mediated by short motifs that dock to surface grooves of PP1. Although PIPs often contain variants of the same PP1 binding motifs, they differ in the number and combination of docking sites. This molecular‐lego strategy for binding to PP1 creates holoenzymes with unique properties. The PP1 binding code can be described as specific, universal, degenerate, nonexclusive and dynamic. PIPs control associated PP1 by interference with substrate recruitment or access to the active site. In addition, some PIPs have a subcellular targeting domain that promotes dephosphorylation by increasing the local concentration of PP1. The diversity of the PP1 interactome and the properties of the PP1 binding code account for the exquisite specificity of PP1 in vivo.